Nilai Cinta Kasih Dalam Novel “Saat-Saat Jauh” Karya Lia Seplia Dan Implikasi Pada Pembelajaran Sastra Di SMA Negeri 3 Palangka Raya - Riska Susanti; Indra Perdana; Paul Diman; Halimatus Sadiah; Dewi Anggraini; Erna Agustina (Universitas Palan, 2023)
This research is descriptive research with a qualitative approach. The data in this research is in the form of the value of love in the novel Moments Deep by Lia Seplia which is arranged in the form of phrases found in the novel. The data collection technique used in this research is literature study. Based on research results, love between men and women is love that is given to each other, the feelings that arise within both of them form a unified whole by, giving sacrifices to the partner by thinking about the interests of the partner, mutual trust between the partners even when they are far apart, and mutual honesty to express feelings. Love for the family occurs between parents and children, children and parents, younger siblings and older siblings and vice versa, or between siblings who have blood ties which includes an attitude of affection, giving attention and care to elderly parents by caring for and loving them, being willing to make sacrifices from parents are to educate and care for a child sincerely until the child grows and develops until now, responsibility in the form of parents can be given in the form of meeting the needs of their children, and others. Love between fellow humans is an effort made by humans by providing assistance or in the form of assistance as social creatures who should work together and lend a hand. Love between humans and God means the form of human faith in God by carrying out His commands and avoiding His prohibitions and surrendering with all sincerity, performing worship, praying for help and convenience for what is done, always being grateful for everything that has been given. His. There are implications for the value of love in the novel Saat- saatjauh by Lia Seplia in learning high school novel texts in the 2013 curriculum.